Chase Meadors: capstone - Meadors, Chase, artist (Colorado State University. Libraries, 2024)
The artist's statement: Isolation, surveillance, and ostracization are themes that my work focuses on. These themes emerged not only throughout my childhood and adolescence but are also fears and concerns I still carry around in my daily life. My past experiences have made me paranoid about being watched, being othered, and being alone. I have chosen to manifest these persistent concerns into my body of art. To create within these themes without letting them overwhelm me, I need to follow a routine in my creation. Music is a must. The feeling of being filled with and surrounded by music breaks down my fears of being observed and lets me delve into my art. My work is both a process of concept influencing materials and vice versa. I work on material exploration while developing concepts, and expand on these concepts using notes, sketches, measurements, and math, then build up from armature to base to skin. With my work, I want to focus on creating a dialogue. I want people to feel something, to think about something, and to discuss something. I am not going to assume what this something is to each person, as long as it exists and causes the viewer to in some way interact personally with the work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: sculpture